2016
DOI: 10.1007/s11116-016-9748-9
|View full text |Cite
|
Sign up to set email alerts
|

Exploring immigrants travel behaviour: empirical findings from Offenbach am Main, Germany

Abstract: This paper focuses on the everyday travel behaviour of immigrants in Germany. We use data from an empirical study conducted in Offenbach am Main, a city with one of the highest immigrant populations in Germany. We compared the travel behaviour of immigrants and their direct offspring to that of Germans without an immigration background. Compared to non-immigrants, immigrants own fewer cars or bicycles per household, and they were also less likely to be able to ride a bicycle or to drive a car and to have acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…They tend to remain in these neighbourhoods and are spatially less mobile within Germany (Şaka, 2013). This coincides with their lower likelihood of owning a car or having access to household vehicles because they are on average less wealthy and creditworthy (e.g., Blumenberg & Smart, 2011;Welsch, Conrad, & Wittowsky, 2018). Carpooling therefore constitutes an affordable means of transportation.…”
Section: The Context: Carpooling In Light Of Immigrationmentioning
confidence: 99%
See 2 more Smart Citations
“…They tend to remain in these neighbourhoods and are spatially less mobile within Germany (Şaka, 2013). This coincides with their lower likelihood of owning a car or having access to household vehicles because they are on average less wealthy and creditworthy (e.g., Blumenberg & Smart, 2011;Welsch, Conrad, & Wittowsky, 2018). Carpooling therefore constitutes an affordable means of transportation.…”
Section: The Context: Carpooling In Light Of Immigrationmentioning
confidence: 99%
“…Language skills can pose a hurdle, particularly among refugees from Syria, Iraq, and Afghanistan (C. Becker, ), whose arrival in Germany peaked in 2015 and who now make up a significant part of the immigrant population (Brücker, Rother, & Schupp, ). In these cases, carpooling constitutes an alternative form of transportation to the less affordable (Steer Davies Gleave, ) and less flexible (in terms of destinations) public transportation in Germany (see also Nielsen, Hovmøller, Blyth, & Sovacool, , on Denmark) that also requires an adequate level of language skills (Welsch et al, ). Thus, discrimination on the carpooling market has severe consequences for immigrants with them being more likely to be spatially, socio‐economically, and socially entrapped.…”
Section: The Context: Carpooling In Light Of Immigrationmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that different cultural norms could also play a role leading to different preferences (or restrictions) and choices. Similarly, a recent German study found a small effect of immigrant status on cycling, when controlling for selected demographic factors (Welsch et al 2018).…”
Section: Introductionmentioning
confidence: 87%
“…The United Kingdom and the Netherlands, however, have received attention [23,24]. Also for the city of Offenbach am Main in Germany, differences in mobility behaviour of immigrants have been analysed [25]. It is striking that the European studies mostly do not differentiate between people with immigrant background and recently settled immigrants.…”
Section: Literature Reviewmentioning
confidence: 99%